Py-GC-MS of refuse materials in waste to energy point of view. (February 2019) - Lokahita, Baskoro; Kurniawan, Winarto; Aziz, Muhammad; Takahashi, Fumitake
Abstract: Thermochemical waste to energy technology could efficiently tackle waste management problem, but it could emit dangerous pollutant if the quality of the feedstock is bad and standard operating condition was not met. Pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) methodology was used to assess the quality of refuse material for solid fuel by identifying the degradation behavior and produced gas in pyrolysis condition. The material used was a mineral water plastic seal (PS), laminated packaging (LP), refuse derived fuel (RDF) and mechanical biological treatment residue (SR). The results show that PS and LP have similar degradation curve since it mainly consists of polypropylene. The gas product characteristic was also similarly consisted of CO, CO2, and hydrocarbon. RDF and SR have more complex degradation curve consist of three peaks. Both are composite material consist of organics, plastics, and inert materials. CO and CO2 are still major pyrolysis gas composition. This work could be developed to build process simulation to simulate real waste to energy plant.